2022
DOI: 10.1371/journal.pone.0273097
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and severe acute respiratory syndrome-coronavirus-2 structural protein-based serology of Mexican children and adolescents with coronavirus disease 2019

Abstract: Severe acute respiratory syndrome (SARS)-coronavirus (CoV)-2 infection in children and adolescents primarily causes mild or asymptomatic coronavirus disease 2019 (COVID-19), and severe illness is mainly associated with comorbidities. However, the worldwide prevalence of COVID-19 in this population is only 1%–2%. In Mexico, the prevalence of COVID-19 in children has increased to 10%. As serology-based studies are scarce, we analyzed the clinical features and serological response (SARS-CoV-2 structural proteins)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…In Mexico, obesity in children is very common and strongly related to COVID-19 and severe illness [ 15 ]. In this population, underlying conditions such as asthma and obesity were also associated with severe COVID-19 [ 11 , 37 ]. A systematic review of critically unwell children and the association with underlying comorbidities showed that those with pre-existing cardiac diseases were critically unwell [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Mexico, obesity in children is very common and strongly related to COVID-19 and severe illness [ 15 ]. In this population, underlying conditions such as asthma and obesity were also associated with severe COVID-19 [ 11 , 37 ]. A systematic review of critically unwell children and the association with underlying comorbidities showed that those with pre-existing cardiac diseases were critically unwell [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This group had clinical follow-ups, and patients were considered convalescent. A study showed that comorbidities in this population play an essential role in the antibody response against SARS-CoV-2 infection [ 11 ]. However, we did not identify a tendency in this population and only found a high incidence of low antibody levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Demographic data included sex and age, and clinical data included patient status, comorbidities, and signs/symptoms. The comorbidities were de ned by Flores-Alanis et al and the signs/symptoms were de ned by Cortés-Sarabia et al [24,59].…”
Section: Methodsmentioning
confidence: 99%